Bayesian analysis of population agglomeration and ecological efficiency in Beijing-Tianjin-Hebei region. (October 2019) - Chen, Jianming; Wei, Na; Zhou, Yanli; Ge, Xiangyu
Abstract: By using 35 cities data directly under the jurisdiction of Beijing-Tianjin-Hebei region, this paper improved Bayesian spatial quantile regression method to explore the relationship between population aggregation and eco-efficiency and its mutual influence under the background of Beijing, Tianjin and Hebei urban agglomeration construction theme. The study found that population aggregation has a significant negative impact on the urban eco-efficiency. In addition, the number of primary schools, the scale of urban economic development and investment in real estate development also have a significant negative impact on urban eco-efficiency. While the number of secondary schools and the number of beds in medical and health institutions has a significant positive impact on urban eco-efficiency.